Alkaloids from Hippeastrum argentinum and Their Cholinesterase-Inhibitory Activities: An in Vitro and in Silico Study - Ortiz, Javier Esteban (2016)
Two new alkaloids, 4-O-methylnangustine (1) and 7-hydroxyclivonine (2) (montanine and homolycorine types, respectively), and four known alkaloids were isolated from the bulbs of Hippeastrum argentinum, and their cholinesterase-inhibitory activities were evaluated. These compounds were identified using GC-MS, and their structures were defined by physical data analysis. Compound 2 showed weak butyrylcholinesterase (BuChE)-inhibitory activity, with a half-maximal inhibitory concentration (IC50) value of 67.3 ± 0.09 μM. To better understand the experimental results, a molecular modeling study was also performed. The combination of a docking study, molecular dynamics simulations, and quantum theory of atoms in molecules calculations provides new insight into the molecular interactions of compound 2 with BuChE, which were compared to those of galantamine.